2003
DOI: 10.2108/zsj.20.1183
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Aspects of Intracellular Proteolytic Processing of Peptide Hormone Precursors: Studies of Proopiomelanocortin Processing

Abstract: In this review, the mechanisms underlying the intracellular processing of peptide hormone precursors, with a focus on proopiomelanocortin (POMC), were discussed on the basis of recent information. POMC as well as other prohormones is processed to active peptides through proteolytic cleavage by prohormone convertases PC1 and/or PC2. However, the cleavage-specificity of PC1 and PC2 in mammals is somewhat different from that in amphibians. From the comparative endocrinological point of view, expression and tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 102 publications
0
37
0
Order By: Relevance
“…The different profiles of ACTH and α-MSH observed after PE remain to be evaluated. One hypothesis could be that E 2 may have different mechanisms of action according to the cell type (melanotrope or corticotrope cell) (Tanaka 2003;Olah et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The different profiles of ACTH and α-MSH observed after PE remain to be evaluated. One hypothesis could be that E 2 may have different mechanisms of action according to the cell type (melanotrope or corticotrope cell) (Tanaka 2003;Olah et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Tanaka S et al [12] reported that proPC2 with 638 amino acid residues (74 kDa) is activated into mature PC2 with 529 amino acid residues (64 kDa) in adequate conditions, such as pH 5.0, other PCs and higher Ca 2+ . The soluble CPE (sCPE) is an exopeptidase that cleaves neuro-endocrinopeptides with C-terminal basic amino acids and produces active forms of peptide hormones and neuropeptides [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs, plasma ACTH and α-MSH, the cortisol/creatinine (RC/C) urine ratio and pituitary MRI were assessed and compared at different time points [58]. In dogs, two convertase enzymes are involved in processing the POMC gene products, one active in anterior pituitary cells secreting ACTH, whereas the other is located in the intermediate-lobe cells secreting α-MSH [59]. Therefore not only ACTH but also α-MSH was assessed.…”
Section: In Vivo Data: Experimental Cushing's Disease In Nude Micementioning
confidence: 99%